2017
DOI: 10.5472/mmjoa.2903.01
|View full text |Cite
|
Sign up to set email alerts
|

Regular swimming before the induction of ulcer ameliorates oxidative gastric damage in rats: The anxiolytic effect of exercise

Abstract: Objectives:To investigate the impact of exercise on ulcerogenesis. Materials and Methods:Gastric ulcer was induced in Wistar albino rats that were either kept sedentary or had swimming exercise for 6 weeks. Under anesthesia, ulcer was induced by applying acetic acid on the stomach serosa, while control rats had sham-operation. On 3rd or 10th days of ulcer induction, anxiety levels were measured and rats were decapitated for measuring serum cortisol level, while gastric tissue samples were obtained for histopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
(59 reference statements)
0
2
0
1
Order By: Relevance
“…Physical activity, which reduces the risk for developing chronic diseases (Alessio et al 2005;Beavers et al 2010), is also regarded as a non-pharmacological approach for reducing ulcer incidence in men (Cheng et al 2000a;Radak et al 2008). Prolonged moderate-intensity exercise, in contrast to acute and intensive exercise, was proven to reduce gastric mucosal damage and alleviate the stress response with reductions in the circulating levels of cortisol (Cheng et al 2000b;Bahadir et al 2016;Shephard, 2017). Although exercise was found to increase serum oxytocin levels (Irianti et al 2017) and peripheral administration of oxytocin was reported to exert an anti-ulcer activity (Asad et al 2001b), the role of oxytocin in the protective effect of exercise on gastric ulcer has not yet been evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical activity, which reduces the risk for developing chronic diseases (Alessio et al 2005;Beavers et al 2010), is also regarded as a non-pharmacological approach for reducing ulcer incidence in men (Cheng et al 2000a;Radak et al 2008). Prolonged moderate-intensity exercise, in contrast to acute and intensive exercise, was proven to reduce gastric mucosal damage and alleviate the stress response with reductions in the circulating levels of cortisol (Cheng et al 2000b;Bahadir et al 2016;Shephard, 2017). Although exercise was found to increase serum oxytocin levels (Irianti et al 2017) and peripheral administration of oxytocin was reported to exert an anti-ulcer activity (Asad et al 2001b), the role of oxytocin in the protective effect of exercise on gastric ulcer has not yet been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…A moderate level of exercise was shown to exert beneficial effects by fine-tuning ROS production (Peternelj & Coombes, 2011;Bouzid et al 2018) and by the activation of adaptive anti-oxidant enzymes (superoxide dismutase, catalase and glutathione peroxidase, etc. ), which prepare the gastric mucosa for any upcoming injurious events (Navarro et al 2004;Ji et al 2006;Bahadir et al 2016;Simioni et al 2018). However, hormonal mechanisms that could mediate the beneficial effects of exercise on the prevention of gastric ulcer have not been fully described yet.…”
Section: Introductionmentioning
confidence: 99%
“…На сегодня моделированию язв желудка посвящено достаточно большое количество научных работ [1,2,3,4,5]. Наиболее часто применяется способ моделирования язвы желудка, предложенный S. Okabe et al [6,7].…”
Section: Introductionunclassified